Development and usability evaluation of a mHealth application for prehospital triage - Elham Asadiara; Hassan Emami; Mehdi Safari; Reza Rabiei (Scientific Reports)
Abstract This study developed and evaluated a mobile health (mHealth) application for prehospital triage. The effective triage of undifferentiated patients is crucial for appropriate prehospital care and mHealth applications offer potential support by classifying patient conditions prior to hospital arrival. This two-stage applied study, conducted in 2023, began with determining functional requirements through a literature review and a questionnaire-based survey, informed by existing guidelines. A conceptual model was then developed using Microsoft Visio 2021. The application then was developed using Android Studio in Java and Kotlin languages. In the second stage, the application’s usability was evaluated by involving 32 paramedics and EMT technicians through using the Mobile Application Usability Questionnaire (MAUQ). Key application features included comprehensive information forms, triage level calculation based on the Revised Trauma Score (RTS), hospital navigation, and structured case report generation. Ease of use received the highest score (4.35 ± 0.47), while interface and satisfaction obtained the lowest scored (3.84 ± 0.79). Overall user satisfaction was high (4.12 ± 0.59; Max: 5.00). Results suggest that this mHealth application can effectively support prehospital care by addressing user needs and providing essential functionalities.